Pengelolaan Keuangan dan Sumber Daya Manusia di Nagari Kamang Hilia: Financial and Human Resource Management in Kamang Hilia Village - Nelvirita, Nelvirita; Afriyenti, Mayar; Arza, Fefri Indra; Mulyani, Erly; Fitra, Halkadri; Fawziah, Intan Nurbaiti; Raga, Ridha Azka (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Financial and human resource management in Nagari plays a crucial role in establishing transparent, accountable, and sustainable village governance. Nagari Kamang Hilia in Agam Regency faces challenges, including limited understanding of financial regulations among officials, low financial literacy among the community, and inadequate human resource skills. This community service program was carried out to enhance the capacity of Nagari officials to manage village funds, prepare financial reports, and strengthen human resource management. The methods applied included training, mentoring, discussions, and demonstrations involving lecturers and students from Universitas Negeri Padang, as well as nagari officials. The results indicate that participants gained a solid understanding of the material, updated their knowledge on financial management and human resource administration, and acknowledged the program’s benefits in improving professionalism. However, participants found the training duration insufficient, suggesting the need for additional sessions. In conclusion, this program strengthened financial governance and human resource development in the Nagari, while also fostering synergy between higher education institutions and local government to promote community development through knowledge transfer.